A method for evaluating tram stops based on passenger expectations and the needs of disabled persons - Podciborski, Tomasz (International Conference “Environmental Engineering”, 2017)
Criteria against which assessment is carried out the operation of public transport generally refer to specific elements of the network of public transport, such as lines, vehicles, bus stops, etc. Criteria for evaluation and their types can be many and they can have diverse nature (Saaty 1995). The main aim of this study was to develop a method for evaluating tram stops based on passenger expectations and the needs of disabled persons. This consisted in developing the list of items to be evaluated and principles of assessment. The proposed method was verified in selected sites, and the results of the assessment are discussed in the paper. The surveyed sites were tram stops in the city of Olsztyn in north astern Poland. The main aim was achieved through detailed goals, including definition of the concept of municipal transport, description of infrastructure components that influence the quality, attractiveness and safety of the analyzed tram stops, presentation of evaluation indicators and the relevant criteria, and description of evaluation principles.
Keywords: municipal transport; public transport; ram stops